2012
DOI: 10.4236/oji.2012.23014
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels and T lymphocyte subsets in pregnant women with eclampsia

Abstract: Background: Eclampsia, defined as the occurrence during pregnancy of hypertension, oedema, proteinuria and/or other neurologic abnormalities, causes substantial morbidity and mortality for both mother and foetus. However, its aetiology is largely unknown. Genetic and immune factors may play a role including a reduced maternal response to paternal antigen and an altered adaptation of the maternal immune system to the foetus. Methods: Participants consisted of pregnant women with and without a diagnosis of eclam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…In contrast to the current study findings, Musa et al, 2012, 19 observed that levels of CD3+ T cells and CD4+ T cells in pre-eclamptic patients were significantly lower than those of pregnant controls. Additionally, contrary to our findings, CD3+ and CD4+ T cells were lower in eclampsia and pregnant controls as compared to non-pregnant controls.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the current study findings, Musa et al, 2012, 19 observed that levels of CD3+ T cells and CD4+ T cells in pre-eclamptic patients were significantly lower than those of pregnant controls. Additionally, contrary to our findings, CD3+ and CD4+ T cells were lower in eclampsia and pregnant controls as compared to non-pregnant controls.…”
Section: Discussioncontrasting
confidence: 99%
“…This result agrees with the findings of Musa et al [16] and Anim-Nyame et al [17] who reported higher levels of TNFαand decreased levels ofIL-10in the sera of women with EC compared withpregnantand non pregnant controls. These researchers, however, did not assay for IL-2 and IL-4 in their studies.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the CD4/CD8 ratio in EC was significantly lower than in PC and NPC (p < 0.05) indicating increased CD8+ immune response in EC. This is similar to the reports of Musa et al [18] and Tallon et al [19] where absolute numbers of total T cells (CD3+ T) cells and T helper (CD4+ T) cells decreased significantly in the third trimester of eclamptic women compared to PC and NPC. Other previous work on T lymphocyte enumeration in pregnancy has produced inconsistent results showing decrease [20], increase [21] or no change [22].…”
Section: Discussionsupporting
confidence: 92%